More mixed-integer linear programming models for solving three-stage remanufacturing system scheduling problem - Wang, Wenjie; Tian, Guangdong; Luo, Mengqi; Zhang, Honghao; Yuan, Gang; Niu, Kejia (Computers & industrial engineering, 2024)
•Disassembly, reprocessing and reassembly production stages are integrated.•An efficiency-oriented 3 T-RSSP is investigated and theoretically analyzed.•Four different MILP models based on different modeling ideas are formulated.•Small, medium and large-scaled instances are designed to evaluate MILP models. This paper aims to deal with the three-stage remanufacturing system scheduling problem (3T-RSSP) that minimizes the maximum completion time i.e., makespan. To this end, inspired by distinct modeling ideas, four mixed-integer linear programming (MILP) models are formulated. The modeling ideas used in this paper are sequence-based idea, position-based idea, time-based idea, and adjacent sequence-based idea. Numerical experiments are executed on a set of small-scaled, medium-scaled and large-scaled instances to test the performance of these formulated MILP models in terms of size complexity and computation complexity. Experimental results demonstrate that the sequence-based MILP model (Model 1) is the most efficient one while the time-based MILP model (Model 3) is worst one. The Wilcoxon signed-rank test is also conducted to evaluate the four models. Model 1 is further compared with different optimization solvers, heuristic and some state-of-art heuristics. Comparison results verify the effectiveness and good portability of the MILP model. Moreover, some key parameters contained in 3T-RSSP including end-of-life (EOL) products count, reprocessing lines count, disassembly workstations/reassembly workstations count are also evaluated. Notably, it is concluded that the increase of disassembly workstations/reassembly workstations count can improve the three-stage remanufacturing system’s flexibility and contribute to the enhancement of production efficiency.